ANALISIS GOOD CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP KEBERADAAN KOMITE MANAJEMEN RISIKO INDEPENDEN (SEPARATE RISK MANAGEMENT COMMITTEE) PADA PERUSAHAAN YANG LISTING DI BEI - Andalan Tri Ratnawati; Setyobudi Setyobudi (FEB UNTAG Semarang, 2013)
ABSTRACT This study aims to obtain empirical evidenceregarding the factors that affect the existence of the Separate Risk Management Committee (SRMC), which includes the independent commissioner, board size, auditor reputation, The company complexity, financial reporting risk, leverage and firm size of the existence of SRMC, the company non banking a listing on the Indonesia Stock Exchange. The population in this study were non banking company which listed on Indonesia Stock Exchange (BEI) in 2009-2011. Based on purposive sampling method, the number of samples in this study of 255. Testing hypotheses using regression analysis Logistics. Logistics regression analysis found that there was a board size significant impact on SRMC and the effect of firm size has positive and significant impact on the SRMC non banking companies listed on the BEI. The proportion of independent board, auditor reputation, financial reporting risk, complexity, and leverage does not effect the existence of RMC and the SRMC on non banking companies listed on the Indonesia Stock Exchange.